The right to assemble in Malaysia: the sword and the shield of the Peaceful Assembly Act 2012 / Mazlina Mohamad Mangsor@Mansoor ... [et al.] - Mohamad Mangsor@Mansoor, Mazlina; Hamin, Zaiton; Mansoor, Mazlifah (2014)
The freedoms to assemble, to picket and to parade are vital characteristics of a liberal democratic set-up. In reality, the exercise of the right to assemble by some groups of people may cause the threat to public order. Striking a balance between the shield of promoting the freedom to assemble and the sword of maintaining public order is a problem faced by the regulators. In Malaysia, this conflict is evidenced by a series of arrests and charges against few influential people. The introduction of the Peaceful Assembly Act 2012 (PAA) is anticipated to provide a shield for the citizens and to improve the status quo under section 27 of the Police Act 1967. This paper argues that the Malaysian legal approach for freedom to assemble still raised concerns of the infringement of the right to freedom of assembly under the new scheme and that such concern requires the urgent attention and action from the relevant authorities. The paper aims to examine the extent of the promotion of the right to assemble and the instrumental aspects of the PAA. The paper also discusses the constitutional perspective of the right to assemble in Malaysia, the historical position of section 27 of the Police Act 1967 and the normative facets of the PAA. Based on a qualitative and doctrinal research method, the paper analyses the secondary data of which the PAA is the primary source. The secondary sources for this article include decided cases, articles in academic journals, books and online databases.